Hope Without Borders: Psychosis, polypharmacy and the future of care? (Existential Analysis: Journal of the Society for Existential Analysis, 2024)
This paper explores the concept of treatment and healing in the twenty-first century, emphasising the importance of open-heartedness and more humanistic and compassionate approaches in psychotherapy. Drawing from the work of R.D. Laing, it critiques the continued over-reliance on pathologising, theorising and commodification in mental healthcare. Instead, it advocates for authentic care characterised by openness, spontaneity, accessibility and directness, aligning with an existential psychoanalytic sensibility.
Keywords: Psychosis; polypharmacy; existential psychoanalysis; McDonaldization